The conundrum of asymptomatic carotid stenosis—determinants of decision and evidence - Fernandes e Fernandes, José (Ann Transl Med, 2020)
Management of asymptomatic carotid disease continues to challenge medical practice and present evidence is often conflicting. Stroke is a significant burden in Public Health and 11% to 15% appear as first neurologic event associated with asymptomatic carotid stenosis. Randomized trials provided support for Guidelines and Recommendations to intervene on asymptomatic stenosis, but at a known cost of a high number of unnecessary operations. Conflicting evidence from natural history studies and the widespread use of proper medical management including risk factors control, lowering-lipid drugs and strict control of arterial hypertension have reduced the incidence of strokes associated to asymptomatic carotid disease challenging established practice. Need to identify vulnerable lesions prone to develop thromboembolic brain events and also vulnerable patients at a higher risk of stroke is necessary and essential to further improve effectiveness of our interventions. After review of published literature on natural history of asymptomatic carotid stenosis, diagnostic methods to identify plaque vulnerability and present-day results of both endarterectomy and stenting, a strategy for management of asymptomatic carotid stenosis is suggested aiming to reduce unnecessary interventions and effectively contribute to stroke prevention.